A sampling theorem by perturbing the zeros of a sine-type function. Issue 14 (26th October 2021) - Al-Hammali, Hussain; Faridani, Adel
ABSTRACT: In this paper, we present a generalisation of the classical Shannon sampling theorem that allows for sampling sets that are perturbations of the set of zeros of a sine-type function. Such sampling sets may be non-equidistant and non-periodic.